Preparation method and application of bifunctional composite membrane material based on hollow conjugated microporous polymer microsphere loaded titanium dioxide

By introducing a dual-function composite film material with hollow conjugated microporous polymer microspheres supported by titanium dioxide into the photocatalyst, the shortcomings of existing photocatalysts in terms of photocatalytic activity and resource utilization efficiency are solved, and the organic pollutants in water are realized. Efficient degradation and antibacterial properties.

CN119455678APending Publication Date: 2025-02-18NORTHWEST UNIVERSITY FOR NATIONALITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411431876.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing photocatalysts such as titanium dioxide have shortcomings in photocatalytic activity and resource utilization efficiency, making it difficult to efficiently remove organic pollutants in water and effectively utilize solar energy.

Method used

Using a dual-function composite film material based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide, the preparation method of cross-coupling, hard template method and sodium alginate cross-linking film formation is constructed to construct efficient organic-inorganic heterostructured light. catalyst.

Benefits of technology

It realizes efficient photocatalytic degradation and antibacterial properties of organic pollutants in water, improves the spectral response and stability of the photocatalyst, and has good hydrophilic wetting and recycling capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455678A_ABST
    Figure CN119455678A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of photocatalytic membrane materials, in particular to a preparation method of a bifunctional composite membrane material based on hollow conjugated microporous polymer microsphere loaded titanium dioxide, which comprises the following steps: preparing pyrenyl conjugated microporous polymer hollow spheres; preparing a carbonized pyrenyl conjugated microporous polymer hollow sphere; and preparing two pyrenyl conjugated microporous polymer hollow sphere membrane materials. The invention also provides an application of the bifunctional composite membrane material based on the hollow conjugated microporous polymer microsphere loaded titanium dioxide in the aspects of photocatalytic degradation and photocatalytic bacteriostasis. The invention discloses a preparation method of a bifunctional composite membrane material based on hollow conjugated microporous polymer microsphere loaded titanium dioxide, which can photocatalytically degrade organic pollutants in water and can realize photocatalytic bacteriostasis, by taking cross coupling, a hard template method and sodium alginate cross-linking membrane formation as main means.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalytic film material preparation, and in particular to a preparation method and application of a dual-functional composite film material based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide. Background Art

[0002] Technological progress and industrial development have greatly promoted global economic growth and social progress, but have also exacerbated water pollution and energy crisis problems. During this period, a large amount of waste has been discharged into the aquatic environment. Among them, organic compounds are considered to be one of the most difficult pollutants to degrade due to their disadvantages such as toxicity and difficulty in degradation. For example, dyes not only inhibit photosynthesis and oxygen exchange of aquatic plants and animals by blocking the penetration of light, but also endanger human health and even cause cancer. Incomplete absorption and partial metabolism of antibiotics in organisms lead to residues in water, which are potentially harmful to human health. In order to protect human health and biodiversity from these organic compounds, many treatment methods have been developed. However, traditional treatment methods (such as physical, chemical and biological methods) have various limitations, such as time-consuming, high cost and possible secondary pollution. Solar energy is an ubiquitous and inexhaustible energy source that can fully meet the global energy demand. Photocatalysis is the most emerging technology due to its advantages such as eco-friendly and energy-saving requirements. Therefore, photocatalytic degradation of organic pollutants in water is of great significance to sustainable development and environmental protection.

[0003] It is an effective strategy to achieve efficient utilization and conversion of solar energy by constructing good photocatalysts. The study of titanium dioxide (TiO2) as a photocatalyst began in the 1970s. However, due to the wide band gap and rapid carrier recombination of TiO2, its photocatalytic activity is low. In addition, TiO2 is easily challenged by high aggregation. Although the band gap range can be narrowed by chemical modification or changing the crystal structure of the catalyst, so that TiO2 can be excited in the visible or near-infrared range. However, most of the solar energy reaching the earth's surface is not utilized, which not only hinders the removal of organic pollutants from water, but also is a waste of resources. In order to improve the photocatalytic performance of photocatalysts, heterostructures based on porous organic polymers and metal semiconductors have been increasingly studied. Metal-free conjugated microporous polymers (CMPs) have tunable electronic structures, controllable band gaps, and high surface areas, which can be used to design ideal photocatalysts with targeted optical structures and catalytic properties. Therefore, doping conjugated microporous polymers and TiO2 can construct efficient organic-inorganic catalysts. It not only enhances the photocatalytic activity and spectral response, but also prevents the rapid recombination of photogenerated electrons and holes. Furthermore, as a building block, the large π conjugation and electron delocalization of pyrene enable fast charge transport and excellent optical physical properties. In particular, in pyrene-based CMPs, the planar conjugation of the pyrene block acts as a light-harvesting center, allowing the molecule to exhibit efficient visible light absorption properties. Photogenerated electrons and holes are transferred through covalent bond "bridges", which prevents their rapid recombination. Therefore, this has become a common building block for the construction of new CMPs photocatalysts. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a method for preparing a dual-functional composite membrane material based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide and its application.

[0005] In order to achieve the above purpose, the technical solutions provided are as follows:

[0006] A method for preparing a dual-functional composite membrane material based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide, characterized in that it comprises the following steps:

[0007] Step 1: Preparation of pyrene-based conjugated microporous polymer hollow spheres, specifically comprising the following steps:

[0008] First, SiO2 powder, CuI and Pd(PPh3)2Cl2 were added to a reactor with a branched grinding mouth, toluene and Et3N were added under N2 protection, and the mixture was ultrasonically dispersed for 30 minutes, and then 1,3,5-triethynylbenzene and 1,3,6,8-tetrabromopyrene were added;

[0009] Then, after reacting at 90°C and stirring for 48 hours, the mixture was washed with appropriate amounts of chloroform, acetone, and methanol and subjected to Soxhlet extraction with methanol for 3 days;

[0010] Finally, a certain amount of dried powder was placed in a mixed solution of methanol, deionized water, and hydrofluoric acid for etching and then dried at 60 °C to obtain pyrene-based conjugated microporous polymer hollow spheres, named Py-CMPs-HS;

[0011] Step 2: Preparation of carbonized pyrene-based conjugated microporous polymer hollow spheres, specifically comprising the following steps:

[0012] First, a certain amount of Py-CMPs-HS was placed in a quartz tube furnace;

[0013] Then, the mixture was heated to 600°C at a rate of 5°C per minute under nitrogen protection;

[0014] Finally, the product carbonized pyrene-based conjugated microporous polymer hollow spheres were obtained at 600 °C for 2 h, named Py-CCMPs-HS;

[0015] Step 3: Preparation of two pyrene-based conjugated microporous polymer hollow sphere membrane materials, specifically comprising the following steps:

[0016] First, equal masses of Py-CMPs-HS or Py-CCMPs-HS and TiO2 were mixed evenly in an agate mortar, and then an appropriate amount of sodium alginate solution was added;

[0017] Then, the mixed solution was poured onto an organic filter membrane for vacuum filtration, and sodium alginate solutions of different mass fractions were slowly dripped in until no solution could be filtered out;

[0018] Finally, the membrane was immersed in a solution of calcium chloride for crosslinking for several hours and was named Py-CMPs-HS-M or Py-CCMPs-HS-M.

[0019] Preferably, in step 1, the molar ratio of 1,3,5-triethynylbenzene to 1,3,6,8-tetrabromopyrene is 3:4.

[0020] Preferably, in step 2, the volume (mL) ratio of methanol, deionized water and hydrofluoric acid is 4:2:1.

[0021] Preferably, in step 2, the etching time is 4 hours.

[0022] Preferably, in step three, the mass ratio of the pyrene-based conjugated microporous polymer hollow spheres to TiO2 is 1:1.

[0023] The present invention also provides an application of a dual-functional composite membrane material based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide in photocatalytic degradation and photocatalytic antibacterial.

[0024] Preferably, a dual-functional composite membrane material based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide is placed in wastewater containing dyes or antibiotics or in water containing bacterial liquid for experiment.

[0025] The present invention also provides an application of a dual-function composite membrane material based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide in photocatalysis and antibacterial properties.

[0026] Preferably, the membrane material based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide is placed in a bacterial solution containing Escherichia coli or Staphylococcus aureus and irradiated with a xenon lamp (λ>420nm).

[0027] The beneficial effects of the present invention are as follows: the present invention firstly introduces a preparation method of a bifunctional composite membrane material based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide, which can photocatalytically degrade organic pollutants in water and achieve photocatalytic antibacterial properties, using cross-coupling, hard template method and sodium alginate cross-linking film formation as the main means. Through the study of its application, it is preliminarily believed that the composite membrane material prepared in the present invention that can achieve photocatalytic degradation and antibacterial properties has good hydrophilic wettability, high photocatalytic degradation efficiency and antibacterial properties, and has a certain reference value for the organic-inorganic heterojunction strategy that combines photocatalysis with membrane technology in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The invention provides a preparation route for the pyrene-based conjugated microporous polymer hollow microspheres loaded with titanium dioxide hydrogel membrane capable of photocatalytically degrading dyes and antibiotics.

[0029] Figure 2 In the figure, a and b are the FT-IR spectra of Py-CMPs-HS and 13 C nuclear magnetic resonance spectrum; c and d are the XPS full scan spectrum and C1s spectrum of Py-CMPs-HS; e and f are the TGA and XRD patterns of Py-CMPs-HS.

[0030] Figure 3 In the figure, a is the N2 isothermal adsorption / desorption isotherm of Py-CMPs-HS (BET analysis); b is the pore size distribution curve of Py-CMPs-HS (BJH theoretical calculation); c is the FT-IR spectrum of various membranes; d is the XRD diagram of various membranes.

[0031] Figure 4In the figure, a and b are transmission electron microscope images of Py-CMPs-HS and Py-CMPs-HS / TiO2-M; c is a scanning electron microscope image of Py-CMPs-HS / TiO2-M; d and e are energy dispersive spectrometer images of Py-CMPs-HS / TiO2-M.

[0032] Figure 5 In the figure, a-f are water contact angle images of various films.

[0033] Figure 6 In the figure, a is the infrared image of various film materials; b is the surface temperature change of various film materials; c is the temperature change when no material is added and Py-CMPs-HS / TiO2-M treats Rhodamine B.

[0034] Figure 7 In the figure, a and b are the curves of photocatalytic degradation of RhB and TC by organic filter membranes; c and d are the curves of photocatalytic degradation of RhB and TC by different membranes; e and f are the kinetic studies of photocatalytic degradation of RhB and TC by different membranes; g and h are the degradation rates of photocatalytic degradation of RhB and TC by different membranes.

[0035] Figure 8 In the figure, ab are the photocatalytic performance of Py-CMPs-HS / TiO2-M at different RhB and TC concentrations; cf are the kinetic diagrams and rate constants of Py-CMPs-HS / TiO2-M for RhB and TC; gh are the cyclic photodegradation experiments of RhB and TC.

[0036] Fig. 9 In the figure, a is the UV-visible spectra of various materials; b is the Tauc plot of various materials; c is the cyclic voltammogram of Py-CMPs-HS / TiO2; d is the cyclic voltammogram of.

[0037] Fig.10 In the figure, a is the electrochemical impedance spectra of various materials; b is the transient photocurrent response of various materials; cd are the active species capture experiments to degrade RhBh and TC.

[0038] Fig.11 In the figure, a and b are the antibacterial properties of Py-CMPs-HS / TiO2-M against Escherichia coli; cd are the antibacterial properties of Py-CMPs-HS / TiO2-M against Staphylococcus aureus. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example 1

[0041] The preparation method of the pyrene-based conjugated microporous polymer hollow microspheres loaded with titanium dioxide hydrogel film capable of photocatalytically degrading dyes and antibiotics is as follows: Figure 1 shown.

[0042] Figure 1 The invention provides a preparation route for the pyrene-based conjugated microporous polymer hollow microspheres loaded with titanium dioxide hydrogel membrane capable of photocatalytically degrading dyes and antibiotics.

[0043] The specific preparation method of the pyrene-based conjugated microporous polymer hollow microspheres loaded with titanium dioxide hydrogel membrane material capable of photocatalytically degrading dyes and antibiotics is as follows:

[0044] Example 1 Preparation of two pyrene-based conjugated microporous polymer hollow spheres

[0045] (1) Preparation of pyrene-based conjugated microporous polymer hollow spheres (Py-CMPs-HS)

[0046] SiO2 powder (5.85mmol, 351mg), Pd(PPh3)2Cl2 (0.02mmol, 14mg) and CuI (0.0065mmol, 2mg) were added to a reaction tube with a ground mouth and placed under N2 atmosphere. Toluene (15mL) and triethylamine (15mL) were added, and ultrasonic reaction was carried out for 30min. Then 1,3,6,8-tetrabromopyrene (0.3mmol, 77mg) and 1,3,5-triethylbenzene (0.4mmol, 30mg) were added, and magnetic stirring was carried out at 90℃ for 48h under nitrogen protection. Subsequently, the crude product was washed with methanol, acetone, chloroform and water. Soxhlet extraction was carried out with methanol for 72h. Finally, the dried product (250mg) was weighed in a polytetrafluoroethylene beaker and then etched in a mixed solution of methanol (20mL), deionized water (15mL) and hydrofluoric acid (7.5mL) for 4h. After etching, the substrate was washed with appropriate amounts of acetone, water and methanol in turn, and dried to obtain a powdery material named Py-CMPs-HS.

[0047] (2) Preparation of carbonized pyrene-based conjugated microporous polymer hollow spheres (Py-CCMPs-HS)

[0048] A certain amount of Py-CMPs-HS was placed in a quartz tube furnace and heated to 600°C at a heating rate of 5°C per minute under nitrogen protection. The temperature was maintained at 600°C for 2h. The resulting product was named Py-CCMPs-HS.

[0049] (3) Preparation of two pyrene-based conjugated microporous polymer hollow sphere membrane materials

[0050] 10 mg of Py-CMPs-HS and 10 mg of TiO2 were placed in an agate mortar. 2 mL of 1 wt% sodium alginate solution was gradually added while grinding until the two were completely mixed. The mixed solution was then poured into a vacuum filtration device, and an organic filter membrane was selected as the filter membrane. During the filtration process, about 10 mL of 0.5 wt% sodium alginate solution was dripped until no solution seeped out of the membrane. Finally, a black film with a diameter of 4.5 cm was obtained. The membrane was then immersed in a solution containing 20 mL of 1.5 wt% calcium chloride to crosslink the membrane. This process was completed after several hours, and the composite membrane at this time was named Py-CMPs-HS-M. The resulting materials were named Py-CCMPs-HS-M and Py-CCMPs-HS / TiO2-M.

[0051] Figure 2 In the figure, a and b are the FT-IR spectra of Py-CMPs-HS and 13 C NMR spectrum. c and d are the XPS full scan spectrum and C1s spectrum of Py-CMPs-HS. e and f are the TGA and XRD patterns of Py-CMPs-HS.

[0052] Figure 2 The elemental composition and chemical structure of Py-CMPs-HS were characterized by Fourier transform infrared spectroscopy (FT-IR), solid-state 13C nuclear magnetic resonance spectroscopy (13C NMR), X-ray photoelectron spectroscopy (XPS), thermogravimetric analysis (TGA), and X-ray diffraction (XRD). Figure 2 a shows that it is located at 3100cm -1 、2200cm -1 and 1580cm -1 The bands are the stretching vibrations of aromatic hydrocarbons CH, C=C and C≡C in the polymer. Figure 2 b shows that the peak observed between 110 and 140 ppm is attributed to the carbon atoms of the aromatic pyrene units present in the polymer. The signal at 85 ppm corresponds to the carbon atoms of the aromatic pyrene units. Figure 2 cd, it can be seen that the C1s and O1s signals of Py-CMPs-HS are clearly visible, which is consistent with the results of FT-IR. Figure 2 e shows that Py-CMPs-HS has good stability. Figure 2f shows that Py-CMPs-HS has an amorphous structure.

[0053] Figure 3 In the figure, a is the N2 isothermal adsorption / desorption isotherm of Py-CMPs-HS (BET analysis). b is the pore size distribution curve of Py-CMPs-HS (BJH theoretical calculation). c is the FT-IR spectra of various membranes. d is the XRD diagram of various membranes.

[0054] pass Figure 3 The N2 adsorption-desorption isotherms and pore size distribution curves of ab show the coexistence of micropores and mesopores in Py-CMPs-HS. It has a large surface area and uniform pore distribution, which is conducive to providing a large number of photocatalytic active sites. Figure 3 The FT-IR of c shows two characteristic peaks of TiO2, which belong to OH and Ti-O-Ti stretching vibration. It is worth noting that the CO-Ti bond peak appears at 1000cm-1, indicating that CMPs are combined and doped with TiO2. Figure 3 As shown in (d), the diffraction peaks of TiO2 indicate that TiO2 has been successfully doped into the prepared polymer and the functional groups have not changed after carbonization.

[0055] Figure 4 In the figure, a and b are transmission electron micrographs of Py-CMPs-HS and Py-CMPs-HS / TiO2-M. c is a scanning electron micrograph of Py-CMPs-HS / TiO2-M. d and e are energy dispersive spectrometer images of Py-CMPs-HS / TiO2-M.

[0056] Figure 4 ac are SEM and TEM images of Py-CMPs-HS and Py-CMPs-HS / TiO2-M. The surface of Py-CMPs-HS remains intact and still has a complete hollow sphere structure after etching away SiO2. TiO2 is observed to be doped in the form of nanoparticles around Py-CMPs-HS / TiO2-M. Figure 4 de indicates that there are abundant C, O and Ti elements on the surface of Py-CMPs-HS / TiO2-M, while the contents of Na and Ca elements are relatively low.

[0057] Figure 5 In the figure, a-f are water contact angle images of various films.

[0058] Figure 5 af show the water contact angles of various membranes. The hydrophilicity of sodium alginate improves the hydrophobicity of Py-CMPs-HS, enabling it to contact with pollutants in water.

[0059] Figure 6In the figure, a is the infrared image of various membrane materials. b is the surface temperature change of various membrane materials. c is the temperature change when no material is added and Py-CMPs-HS / TiO2-M treats Rhodamine B.

[0060] Figure 6 It can be seen that after 30 minutes of simulated sunlight irradiation, the surface temperature of the membrane after carbonization treatment was the highest, and during the degradation of Rhodamine B, the surface temperature of the Rhodamine B aqueous solution without adding sample materials was higher than that of the surface temperature with Py-CMPs-HS / TiO2-M.

[0061] Example 2 The pyrene-based conjugated microporous polymer hollow microspheres loaded with titanium dioxide hydrogel membrane material capable of photocatalytically degrading dyes and antibiotics and its application in photocatalytic degradation of dye or antibiotic wastewater treatment and photocatalytic antibacterial

[0062] (1) A 500W xenon lamp was used to simulate sunlight (λ>420nm) to perform photochemical degradation experiments on rhodamine B and tetracycline. The hydrogel composite film loaded with 20mg of catalyst was placed in 30mL of tetracycline aqueous solution (10mg L -1 ). In order to ensure that the material reached adsorption equilibrium, the material was treated with a dark reaction for 60 minutes. In addition, a 420-nm cutoff filter was placed on the lens to prevent interference from ultraviolet rays. In the degradation experiment, 2.5 mL of solution was collected every 30 minutes as the sample to be tested. In order to prevent interference from powder samples, a 0.45 μm nylon syringe filter was used for filtration. The residual amounts of rhodamine B and tetracycline were detected at 357 nm and 554 nm by ultraviolet spectrophotometry (UV-4802s).

[0063] Figure 7 In the figure, a and b are the curves of photocatalytic degradation of RhB and TC by organic filter membranes. c and d are the curves of photocatalytic degradation of RhB and TC by different membranes. e and f are the kinetic studies of photocatalytic degradation of RhB and TC by different membranes. g and h are the degradation rates of photocatalytic degradation of RhB and TC by different membranes.

[0064] from Figure 7 adIt can be seen that the degradation rate of RhB by Py-CMPs-HS / TiO2-M can reach 92%, and the degradation rates of Py-CCMPs-HS / TiO2-M, Py-CMPs-HS-M and TiO2-M are 64%, 82% and 28% respectively. The degradation rate of TC can reach 95%, while the degradation efficiencies of Py-CCMPs-HS / TiO2-M, Py-CMPs-HS-M and TiO2-M are 79%, 77% and 45% respectively. Figure 7eh shows that the degradation of rhodamine B and TC by several membranes conforms to the first-order kinetic equation, and the degradation rate constants of Py-CMPs-HS / TiO2-M for RhB are 7.04 times and 1.6 times of those of TiO2-M and Py-CMPs-HS-M, respectively. The degradation rate constants of Py-CMPs-HS / TiO2-M for TC are 4.7 times and 2.1 times of those of TiO2-M and Py-CMPs-HS-M, respectively.

[0065] Figure 8 In the figure, ab are the photocatalytic performance of Py-CMPs-HS / TiO2-M at different RhB and TC concentrations. cf are the kinetic diagrams and rate constants of Py-CMPs-HS / TiO2-M for RhB and TC. gh are the cyclic photodegradation experiments of RhB and TC.

[0066] Figure 8 af show the effect of different pollutant concentrations (10, 15, 20 mg / L) on the photocatalytic performance of Py-CMPs-HS / TiO2-M. It can be seen that with the increase of pollutant concentration, the degradation of RhB and TC showed a downward trend. In addition, through Figure 8 The cyclic photodegradation experiment of gh showed that after three repeated uses, the efficiency of Py-CMPs-HS / TiO2-M for RhB and TC reached 91% and 93%, respectively.

[0067] Fig. 9 In the figure, a is the UV-visible spectra of various materials. b is the Tauc plot of various materials. c is the cyclic voltammogram of Py-CMPs-HS / TiO2. d is the cyclic voltammogram of Py-CMPs-HS.

[0068] pass Fig. 9 From the UV-visible diffuse reflectance spectrum and Tauc curve of a, it can be seen that the absorption of TiO2-M is about 400nm. In contrast, Py-CMPs-HS / TiO2-M has a wider light absorption spectrum ranging from 200-800nm. This shows that it has good light response ability. And the calculated band gap energies of TiO2-M, Py-CMPs-HS-m and Py-CMPs-HS / TiO2-M are 3.20, 2.14 and 2.02eV respectively. Fig. 9 As shown in Figure cd, the calculated LUMO energy levels of Py-CMPs-HS-m and Py-CMPs-HS / TiO2-M are -3.68 eV and -3.61 eV, respectively. The calculated HOMO energy levels of Py-CMPs-HS-m and Py-CMPs-HS / TiO2-M are -5.82 eV and -5.63 eV, respectively.

[0069] Fig.10In the figure, a is the electrochemical impedance spectra of various materials. b is the transient photocurrent response of various materials. cd is the active species capture experiment to degrade RhBh and TC.

[0070] Fig.10 ab are the transient photocurrent response (IT) and electrochemical impedance spectroscopy (EIS) of various materials. It can be seen from the figure that Py-CMPs-HS / TiO2 exhibits the highest photocurrent response, which is consistent with the results of photocatalytic degradation of organic pollutants. The enhancement of the photocurrent response confirms the significant increase in the electron transfer rate after the combination of CMP and TiO2. The arc radius of the EIS curve of Py-CMPs-HS / TiO2 is the smallest, indicating that the separation efficiency of photogenerated electrons and holes is the highest. Therefore, the combination of CMP and TiO2 exhibits excellent photocatalytic performance. Fig.10 cd are the Py-CMPs-HS / TiO2 active material capture experiments. When the energy of the incident light is greater than the band gap energy of the catalyst, the photogenerated electrons (e - ) absorbs light energy and transitions to CB; therefore, the photogenerated holes (h + ) and e - Separation. - and h + Under electric field or diffusion conditions, it contacts the catalyst surface and reacts with H2O or O2 to generate various active oxygen species, such as hydroxyl radicals (·OH), linear oxygen ( 1 O2) and superoxide radicals (·O2 - ).like Fig.10 As shown in cd, disodium ethylenediaminetetraacetate (EDTA-2Na), isopropyl alcohol (IPA), benzoquinone (BQ) and nitrogen (N2) were introduced as h + , OH, O2 - and 1 The results show that the addition of BQ and N2 has the most obvious inhibitory effect on the degradation of RhB, especially BQ. After the addition of BQ, the degradation efficiency of RhB is only 36%, while IPA and EDTA-2Na scavengers have no obvious inhibitory effect on the degradation of rhodamine B. In the process of photocatalytic degradation of tetracycline, BQ and N2 also have an inhibitory effect on the degradation of tetracycline. In the degradation process of TC, the addition of BQ and EDTA-2Na has the most obvious inhibitory effect, followed by N2 scavenger. Therefore, O2 - 、h + and 1 O2 is the main active species in the photodegradation of RhB and TC.

[0071] Fig.11In the figure, a and b are the antibacterial properties of Py-CMPs-HS / TiO2-M against Escherichia coli. cd are the antibacterial properties of Py-CMPs-HS / TiO2-M against Staphylococcus aureus.

[0072] Photocatalytic antibacterial performance of Py-CMPs-HS / TiO2-M against Escherichia coli and Staphylococcus aureus Fig.11 As shown. Without the addition of the membrane, the number of viable bacteria remained relatively stable within 1 hour of observation in a dark environment. However, under light conditions, the number of viable bacteria began to decline. It is worth noting that the colony count remained above 50% of the initial value, indicating the potential for continued survival. However, the addition of Py-CMPs-HS / TiO2-M led to a significant decrease in the number of viable bacteria. The inhibition rates against Escherichia coli and Staphylococcus aureus were 76.74% and 98.90%, respectively.

[0073] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a dual-functional composite membrane material based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide, characterized in that: The steps include: Step 1: Preparation of pyrene-based conjugated microporous polymer hollow spheres, specifically comprising the following steps: First, SiO2 powder, CuI and Pd(PPh3)2Cl2 were added to a reactor with a branched grinding mouth, toluene and Et3N were added under N2 protection, and the mixture was ultrasonically dispersed for 30 minutes, and then 1,3,5-triethynylbenzene and 1,3,6,8-tetrabromopyrene were added; Then, after reacting at 90°C and stirring for 48 hours, the mixture was washed with appropriate amounts of chloroform, acetone, and methanol and subjected to Soxhlet extraction with methanol for 3 days; Finally, a certain amount of dried powder was placed in a mixed solution of methanol, deionized water, and hydrofluoric acid for etching and then dried at 60 °C to obtain pyrene-based conjugated microporous polymer hollow spheres, named Py-CMPs-HS; Step 2: Preparation of carbonized pyrene-based conjugated microporous polymer hollow spheres, specifically comprising the following steps: First, a certain amount of Py-CMPs-HS was placed in a quartz tube furnace; Then, the mixture was heated to 600°C at a rate of 5°C per minute under nitrogen protection; Finally, the product carbonized pyrene-based conjugated microporous polymer hollow spheres were obtained at 600 °C for 2 h, named Py-CCMPs-HS; Step 3: Preparation of two pyrene-based conjugated microporous polymer hollow sphere membrane materials, specifically comprising the following steps: First, equal masses of Py-CMPs-HS or Py-CCMPs-HS and TiO2 were mixed evenly in an agate mortar, and then an appropriate amount of sodium alginate solution was added; Then, the mixed solution was poured onto an organic filter membrane for vacuum filtration, and sodium alginate solutions of different mass fractions were slowly dripped in until no solution could be filtered out; Finally, the membrane was immersed in a solution of calcium chloride for crosslinking for several hours and was named Py-CMPs-HS-M or Py-CCMPs-HS-M.

2. The method for preparing a dual-functional composite membrane material based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide according to claim 1, characterized in that: In step 1, the molar ratio of 1,3,5-triethynylbenzene to 1,3,6,8-tetrabromopyrene is 3:

4.

3. The method for preparing a dual-functional composite membrane material based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide according to claim 1, characterized in that: In step 2, the volume (mL) ratio of the methanol, deionized water and hydrofluoric acid is 4:2:

1.

4. The method for preparing a dual-functional composite membrane material based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide according to claim 1, characterized in that: In step 2, the etching time is 4 hours.

5. The method for preparing a dual-functional composite membrane material based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide according to claim 1, characterized in that: In step three, the mass ratio of the pyrene-based conjugated microporous polymer hollow spheres to TiO2 is 1:

1.

6. Use of any one of the bifunctional composite membrane materials based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide as described in claims 1 to 5 in photocatalytic degradation.

7. The use according to claim 6, characterized in that: A bifunctional composite membrane material based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide was placed in wastewater containing dyes or antibiotics for experiment.

8. Use of any one of the bifunctional composite membrane materials based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide as described in claims 1 to 5 in photocatalytic antibacterial properties.

9. The use according to claim 8, characterized in that: The membrane material based on hollow conjugated microporous polymer microspheres loaded with titanium dioxide was placed in a bacterial solution containing Escherichia coli or Staphylococcus aureus and irradiated with a xenon lamp (λ>420nm).